Effect of environmental conditions and antifungal agents on growth and sporulation of Trichophyton Tonsurans isolated from vertical ringworm in human - Esam Suliman; Waed Jasim (College of Education for Pure Sciences, 2018)
Trichophyton tonsurans was isolated from epidermal scales and infected hairs of infected child with tinea capitis from AL- salam Education Hospital at Mosul city. The fungus was identified according to the morphological characteristics and microscopic features, as well as penetration of the hair by the fungal hyphae Results on the effects of environmental conditions on the growth and sporulation of the pathogen showed that the best medium for optimum growth of the fungus occurred on Potato Dextros Agar (PDA) medium with an average diameter of colonies 88 mm followed by 85.33mm and 82.66mm and 60.00mm for Sabouraud dextrose agar (SDA), Oatmeal agar (OMA) and Trichophyton agar no.4 (TNo.4) respectively. The least growth was observed on Rice agar +tween 80 ( R-t80 ) with 44.66 mm Minimum sporulation of the fungus was detected on SDA and reached 2.84x102 conidia/ml Optimum temperature for the growth of the fungus was 28C̊ with 84.88 mm colony diameter while 62.33 mm at 15C̊. No growth was observed at 35C̊ on (PDA). Average diameter of fungal colonies was 84.66 mm at the optimum pH 5.5, Growth and sporulation of the fungus increased proportionally with incubation period reached maximum after 12 days and gave 88.00 mm and 3.18x102 conidia/m respectively . While the least incubation period was noticed at the 4th day and colony reached 29.33 mm and 1.40x103 conidia/ml sporulation . Testing the efficacy of four antifungal drugs viz - Nystatin ( Nys ), Griseofulvin (GRF), Fluconazol (FLZ) and Itraconazol (ITZ) on the growth and sporulation of T.tonsurans proved that Griseofulvin was the most effective antifungal which cause complete inhibition (100%) at 40 mg/ml followed by Fluconazol and then Itraconazole, while the least effect was detected with Nystatin which gave colony diameter 25.00 mm and 66.33 conidia/ml.